The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/diagnostics12081824
|View full text |Cite
|
Sign up to set email alerts
|

Fast Functional Rehabilitation Protocol versus Plaster Cast Immobilization Protocol after Achilles Tendon Tenorrhaphy: Is It Different? Clinical, Ultrasonographic, and Elastographic Comparison

Abstract: Background: the incidence of Achilles tendon (AT) rupture is rising; however, there is no clear consensus regarding the optimal treatment. The aim of this retrospective study was to compare instrumental and patient-reported outcome scores after fast functional rehabilitation (group A) versus plaster cast immobilization (group B) programs in patients who underwent AT tenorrhaphy. Methods: 33 patients, with similar clinical and demographic features, underwent open AT tenorrhaphy between January and July 2018. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Some ultrasonographic studies have reported that after treatment, the ruptured tendon gradually grows in size in approximately 6 months and the augmented size could be due to a long-lasting remodeling phase. 5,20 Other studies have recommended visualizing and quantifying intratendinous vascularization using power Doppler. They found that the vascularization measured by PD flow activity was increased in the healing tendon at 3 and 6 months and was normalized by 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Some ultrasonographic studies have reported that after treatment, the ruptured tendon gradually grows in size in approximately 6 months and the augmented size could be due to a long-lasting remodeling phase. 5,20 Other studies have recommended visualizing and quantifying intratendinous vascularization using power Doppler. They found that the vascularization measured by PD flow activity was increased in the healing tendon at 3 and 6 months and was normalized by 12 months.…”
Section: Discussionmentioning
confidence: 99%